On a Guiding of Whistler‐Mode Waves by Density Gradients. Issue 12 (8th December 2022) - Streltsov, Anatoly V.
Abstract: Observations from satellites demonstrate that in the magnetosphere, VLF whistler‐mode waves are frequently detected in the narrow transition regions, where the plasma density changes its magnitude over a short distance across the ambient magnetic field. These observations suggest that the small‐scale, isolated density gradients can guide the VLF whistler‐mode waves along the field. We investigate the guiding of the whistler‐mode waves by the transverse density gradients with a size much less than the characteristic perpendicular size of the wave. We found analytical solutions describing these waves in the plasma with a sharp density discontinuity between two homogeneous regions, and confirm with time‐dependent, two‐dimensional simulations that these waves are indeed guided by the discontinuity. Simulations also reveal that the parameters of the guided waves (the frequency and parallel wavelength) relate to the parameters of the plasma. Key Points: Localized packages of VLF whistler‐mode waves are frequently observed by satellites in the vicinity of density gradients We model the guiding of these waves by the density gradients using equations of electron magnetohydrodynamics We show that the whistler‐mode wave can be guided by plasma gradients with a size less than the characteristic transverse size of the wave